A case series exploring the efficacy, secondary failure, paradoxical event & relapse with ustekinumab therapy in chronic plaque psoriasis - Ismail, Rasimah; Jamil, Adawiyah; Md Nor, Norazirah (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2020)
Ustekinumab is an anti-IL12/23 biologic agent used for treatment of psoriasis with excellent efficacy. However, there are therapeutic obstacles such as secondary failure and paradoxical event. Disease relapse upon discontinuation of therapy is common. A case series was performed on patients with chronic plaque psoriasis who received ustekinumab between 2013 to 2018 at a tertiary referral centre. Demographics, clinical characteristics, duration of therapy, efficacy, treatment complications, rate and pattern of relapses were determined from the patients’ medical records. Out of 8 patients, 6 (75%) patients were males. There were 6 (75%) biologic-naïve patients. Median age was 41.5 years (IQR26.8-48.3), median duration of psoriasis was 16.5 years (IQR6.5-23.0). Median duration to achieve Psoriasis Activity and Severity Index (PASI)75 was 16 weeks and median total duration of treatment was 102 weeks. All patients achieved treatment success. PASI75 at week 12 was achieved by 37.5%, a median of 16 weeks was required to achieve at least PASI 75 but 6 (75%) attained PASI 90 by then. One patient (12.5%) developed paradoxical event with pustular and plaques. Secondary failure occurred in 2 (25%) patients. All patients relapsed after treatment discontinuation, relapse occurred at median of 40 weeks. Most (71%) developed plaques on relapse but 25% developed plaques and pustules. All but one patient required further biological agent for treatment of relapse. Ustekinumab was efficacious in all patients. Treatment success was achieved slightly later than standard duration. The rare occurrences of secondary failure and paradoxical were observed. Relapse was inevitable, new onset pustular eruptions featured in relapses.